The effects of stock split announcements on the stock returns in Bursa Malaysia - Chin, Chun How; Wong, Hock Tsen (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study investigated the presence of abnormal returns surrounding stock split announcements and the determinants of cumulative abnormal return and the split factor. This study utilized the financial data of 45 corporations that had exercised stock splits on Bursa Malaysia from the years 2011 to 2015. The dependent variables were cumulative abnormal return for 40 days, cumulative abnormal return for 60 days, and the split factor. The independent variables, dividends per share and earnings per share, represent the signalling hypothesis for the stocks in Malaysia, while the bid-ask spread and the trading volume represent the liquidity hypothesis and the market capitalization, respectively. The significance of abnormal returns surrounding stock split announcements was tested using standardized t-statistics. The determinants of cumulative abnormal return and the split factor were determined based on Ordinary Least-Squares (OLS) multivariate regression and Stepwise Least-Squares. The empirical results show that there was a statistically significant positive abnormal return on day 1 [+1] after the stock split announcements. Dividend per share was found to have a statistically significant relationship with the cumulative abnormal return; thus supporting the signalling hypothesis. Bid-ask spread and trading volume were the main determinants of cumulative abnormal return, supporting the liquidity hypothesis under a different estimation window. Bid-ask spread was the only important determinant for the split factor. The results of this study could help investors and policymakers to design policies to improve the overall market efficiency in Malaysia, particularly to increase the effectiveness of information disclosure regarding Malaysian stocks.